2014
DOI: 10.1007/s40553-014-0025-6
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Phosphorus in Metallurgical Silicon by Rare Earth Elements

Abstract: Removal of phosphorus in metallurgical silicon is one of the crucial steps for the production of SoG-Si feedstock. The possibility of doping rare earth elements for phosphorus removal has in this work been studied both theoretically and experimentally. Thermochemical properties of Ce and Pr monophosphides have first been estimated by ab initio thermodynamic simulations based on density functional theory and the direct phonon method. The reliability of the first principles calculations was assessed by coupling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…[35] that the increasing concentration of element with negative e P Me value can decrease the P segregation coefficient and, therefore, promote the impurity removal in acid leaching. The value of e P Ca ¼ À14:6 measured by Shimpo et al [65] at 1723 K (1450°C) [65] well supports the above explanation and the reported low Gibbs energy of formation of the lanthanide monophosphides [66] also implies the promoted P segregation in the slag-treated alloy. Thus, it is expected that the increasing slag basicity results in higher Ca and La contents in the metal phase, which further promotes the P segregation and benefits its removal in acid leaching.…”
Section: E Acid Leaching Of Slag-treated Alloysupporting
confidence: 76%
“…[35] that the increasing concentration of element with negative e P Me value can decrease the P segregation coefficient and, therefore, promote the impurity removal in acid leaching. The value of e P Ca ¼ À14:6 measured by Shimpo et al [65] at 1723 K (1450°C) [65] well supports the above explanation and the reported low Gibbs energy of formation of the lanthanide monophosphides [66] also implies the promoted P segregation in the slag-treated alloy. Thus, it is expected that the increasing slag basicity results in higher Ca and La contents in the metal phase, which further promotes the P segregation and benefits its removal in acid leaching.…”
Section: E Acid Leaching Of Slag-treated Alloysupporting
confidence: 76%
“…39 Si−REE solvents can also be used to purify Si. Tang et al 40 found that the addition of REEs can enhance the removal of P from Si with hydro-metallurgical treatment. Xi et al 41 reviewed the removal impurities from Si using hydrometallurgical technologies.…”
Section: ■ Introductionmentioning
confidence: 99%